Construction of hierarchical ZnCo2O4@NixCo2x(OH)6x core/shell nanowire arrays for high-performance supercapacitors. Issue 1 (30th November 2015) - Fu, Wenbin; Wang, Yaling; Han, Weihua; Zhang, Zemin; Zha, Heming; Xie, Erqing
Abstract : Hierarchical ZnCo2 O4 @Ni x Co2 x (OH)6 x core/shell nanowire arrays have been successfully constructed for hybrid supercapacitors with outstanding performance. Abstract : Rational design and synthesis of core/shell nanostructures as binder-free electrodes has been believed to be an effective strategy to improve the electrochemical performance of supercapacitors. In this work, hierarchical ZnCo2 O4 @Ni x Co2 x (OH)6 x core/shell nanowire arrays (NWAs) have been successfully constructed by electrodepositing Ni x Co2 x (OH)6 x nanosheets onto hydrothermally grown ZnCo2 O4 nanowires and investigated as a battery-type electrode for hybrid supercapacitors. Taking advantage of the hierarchical core/shell structures and the synergetic effect between ZnCo2 O4 nanowires and Ni x Co2 x (OH)6 x nanosheets, the optimised core/shell electrode exhibits remarkable electrochemical performance with a high areal capacity (419.1 μA h cm −2 ), good rate capability and cycling stability. Moreover, the assembled ZnCo2 O4 @Ni x Co2 x (OH)6 x //activated carbon (AC) hybrid device can be reversibly cycled in a large potential range of 0–1.7 V and deliver a maximum energy density of 26.2 W h kg −1 at 511.8 W kg −1 . Our findings indicate that the hierarchical ZnCo2 O4 @Ni x Co2 x (OH)6 x core/shell NWAs have great potential for applications in energy storage devices.